Spending behaviour among sports event attendees during the 2023 men’s hockey junior world cup, Kuala Lumpur - Isa, Kalam Azad; Mohamad Ishak, Muhamad Amirul; Mohamed Kassim, Nur Atikah; Ab Razak, Rozella; Razak, Fatin; Azemi, Mohd Azharul (GADING Journal for the Social Sciences, 2024)
This study analyses the expenditure patterns of participants at the 2023 Men’s Hockey Junior World Cup in Kuala Lumpur, emphasising the identification of key regions with significant economic impacts. A quantitative survey was conducted with 99 participants to examine their spending behaviours. The results show that expenditures on food, beverages, and personal transportation were the most prominent, highlighting the strong influence of local enterprises in these areas. The study also identifies opportunities for revenue growth through strategic marketing and improved merchandising. Understanding attendee spending patterns is essential for improving financial outcomes in future sports events. This study provides actionable insights for event organisers, local businesses, and policymakers, contributing to the existing literature on the economic impact of sports events.